2010
DOI: 10.1074/jbc.m110.116418
|View full text |Cite
|
Sign up to set email alerts
|

Zmynd15 Encodes a Histone Deacetylase-dependent Transcriptional Repressor Essential for Spermiogenesis and Male Fertility

Abstract: Spermatogenesis is a complex process through which male germ line stem cells undergo a multi-step differentiation program and sequentially become spermatogonia, spermatocytes, spermatids, and eventually spermatozoa. In this process, transcription factors act as switches that precisely regulate the expression of genes that in turn control the developmental program of male germ cells. Transcription factors identified to be essential for normal haploid gene expression all display transcription-activating effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 49 publications
2
38
0
2
Order By: Relevance
“…6). In particular, Prss42/Tessp-2 protein was detected in secondary spermatocytes and spermatids, which indicated that Prss42/ Tessp-2 mRNA was under translational arrest in primary spermatocytes as is often observed for genes expressed during spermatogenesis [47][48][49][50]. This also suggested that Prss42/ Tessp-2 functioned at the late stages of meiosis and/or during antibodies (B, D).…”
Section: The Three Prss/tessp Proteases Have Distinct Roles In Spermamentioning
confidence: 88%
“…6). In particular, Prss42/Tessp-2 protein was detected in secondary spermatocytes and spermatids, which indicated that Prss42/ Tessp-2 mRNA was under translational arrest in primary spermatocytes as is often observed for genes expressed during spermatogenesis [47][48][49][50]. This also suggested that Prss42/ Tessp-2 functioned at the late stages of meiosis and/or during antibodies (B, D).…”
Section: The Three Prss/tessp Proteases Have Distinct Roles In Spermamentioning
confidence: 88%
“…Exome sequencing analysis revealed the causative mutations in both families. The genes are considered to be responsible for infertility in the respective families for several reasons: the mutations are very severe and not found in 180 unrelated subjects (the control panel plus the infertile cohort) tested, and mouse knockout models are azoospermic 21 22. We screened the cohort of infertile men for the two genes plus SPAG7 for mutation but did not find any potentially pathogenic variant.…”
Section: Discussionmentioning
confidence: 99%
“…SPGF14 (MIM 615842) is caused by a heterozygous frameshift mutation in the ZMYND15 gene (MIM 614312). ZMYND15 is suggested to be a histone deacetylase-dependent transcriptional repressor that controls normal temporal expression of haploid genes during spermiogenesis 9. SPGF15 (MIM 616950) is caused by a homozygous splice site mutation in the SYCE1 gene (MIM 611486) 10.…”
Section: Introductionmentioning
confidence: 99%